2020
DOI: 10.1155/2020/6859374
|View full text |Cite
|
Sign up to set email alerts
|

A 90-Day Oral Toxicity Study of the Ethanol Extract from Eupatorium japonicum Thunb and Foeniculum vulgare in Rats

Abstract: Eupatorium japonicum Thunb and Foeniculum vulgare are two of the most widely used folk herbs and constituents in many traditional Chinese herbal formulas. Nonetheless, little toxicological and safety information associated with following daily repeated exposure is obtained according to previous research. The present study was performed to assess the toxicity of ethanol extract from Eupatorium japonicum Thunb and Foeniculum vulgare (EFE) in male rats administered by dietary oral gavage at target doses of 0.39, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The roles of increased proliferation and insufficient apoptosis in the RA joint, which contribute to synovial membrane hyperplasia, have been previously described in this review, while several investigations are focusing on the modulating effects of natural products as well as reactive oxygen species (ROS) in this context. Eupatorium japonicum Thunb (also reported as Eupatorium chinense L.) is a widely used folk herb in many traditional Chinese herbal formulas [ 79 ]. The extract of Eupatorium japonicum Thunb was investigated among others in a study.…”
Section: Resultsmentioning
confidence: 99%
“…The roles of increased proliferation and insufficient apoptosis in the RA joint, which contribute to synovial membrane hyperplasia, have been previously described in this review, while several investigations are focusing on the modulating effects of natural products as well as reactive oxygen species (ROS) in this context. Eupatorium japonicum Thunb (also reported as Eupatorium chinense L.) is a widely used folk herb in many traditional Chinese herbal formulas [ 79 ]. The extract of Eupatorium japonicum Thunb was investigated among others in a study.…”
Section: Resultsmentioning
confidence: 99%
“…The final mean body weights of the female rats group treated at 15, 30, and 60 mg/kg were 206 ± 19.17 g, 196 ± 1.47 g, and 185 g, respectively, as compared to their initial body weight, which was 200 g. The variation in body weights suggests no compound related adverse effects on the body weight of the rats. Moreover, the decrease in body weight was of no toxicological significance, i.e., less than 10% of the mean control value [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers reported that platycodin D, a major saponin component of Platycodi radix, inhibits fat accumulation and adipogenesis [ 45 ]. According to Dai et al [ 28 ], it is generally accepted that a decrease of 10% body weight gain of treated rats, when compared to the control rats, is defined as toxicological significance. However, the differences in body weight and food consumption observed with respect to control in this study were minor, less than 10%, and therefore considered to be without toxicological relevance.…”
Section: Discussionmentioning
confidence: 99%